Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Kegunaan terhadap Minat Nasabah BRI Menggunakan Mobile Banking Brimo di Bonepantai - Rahman, Endi; Ismail, Yulinda L; Kiayi, Dewi Fajri Januar (J-MAS (Jurnal Manajemen dan Sains), 2025)
This study aims to: (1) determine and analyze whether there is an effect of Perceived Ease of Use on BRI Customers' Interest in Using BRImo Mobile Banking, (2) determine and analyze whether there is an influence of Perceived Usefulness on BRI customers' interest in using BRImo Mobile Banking, and (3) determine and analyze whether there is an influence of Perceived Ease of Use and Perceived Usefulness on BRI customers' interest in using BRImo Mobile Banking. This study used a quantitative approach with data collection techniques through questionnaires. The sampling technique used purposive sampling with 100 respondents, which was determined using the Yamane formula. Data analysis was performed using multiple linear regression. The results of the study show that: (1) partially, the perception of ease of use has a positive and significant effect on customer interest in using BRImo, (2) partially, the perception of usefulness also has a positive and significant effect on customer interest in using BRImo, and (3) simultaneously, the perception of ease of use and the perception of usefulness have a positive and significant effect on customer interest in using BRImo. The contribution of these two variables to customer interest in using BRImo is 57.9%, while the remaining 42.1% is influenced by other factors outside the scope of this study.